Late Glacial and Holocene vegetation and lake changes in SW Yakutia, Siberia, inferred from sedaDNA, pollen, and XRF data - Baisheva, Izabella; Biskaborn, Boris K.; Stoof-Leichsenring, Kathleen R.; Andreev, Andrei; Heim, Birgit; Meucci, Stefano; Ushnitskaya, Lena A.; Zakharov, Evgenii S.; Dietze, Elisabeth; Glückler, Ramesh; Pestryakova, Luidmila A.; Herzschuh, Ulrike (Frontiers in Earth Science, 2024)
Only a few palaeo-records extend beyond the Holocene in Yakutia, eastern Siberia, since most of the lakes in the region are of Holocene thermokarst origin. Thus, we have a poor understanding of the long-term interactions between terrestrial and aquatic ecosystems and their response to climate change. The Lake Khamra region in southwestern Yakutia is of particular interest because it is in the transition zones from discontinuous to sporadic permafrost and from summergreen to evergreen boreal forests. Our multiproxy study of Lake Khamra sediments reaching back to the Last Glacial Maximum 21 cal ka BP, includes analyses of organic carbon, nitrogen, XRF-derived elements, sedimentary ancient DNA amplicon sequencing of aquatic and terrestrial plants and diatoms, as well as classical counting of pollen and non-pollen palynomorphs (NPP). The palaeogenetic approach revealed 45 diatom, 191 terrestrial plant, and 65 aquatic macrophyte taxa. Pollen analyses identified 34 pollen taxa and 28 NPP taxa. The inferred terrestrial ecosystem of the Last Glacial comprises tundra vegetation dominated by forbs and grasses, likely inhabited by megaherbivores. By 18.4 cal ka BP a lake had developed with a high abundance of macrophytes and dominant fragilarioid diatoms, while shrubs expanded around the lake. In the Bølling-Allerød at 14.7 cal ka BP both the terrestrial and aquatic systems reflect climate amelioration, alongside lake water-level rise and woodland establishment, which was curbed by the Younger Dryas cooling. In the Early Holocene warmer and wetter climate led to taiga development and lake water-level rise, reflected by diatom composition turnover from only epiphytic to planktonic diatoms. In the Mid-Holocene the lake water level decreased at ca. 8.2 cal ka BP and increased again at ca. 6.5 cal ka BP. At the same time mixed evergreen-summergreen forest expanded. In the Late Holocene, at ca. 4 cal ka BP, vegetation cover similar to modern conditions established. This study reveals the long-term shifts in aquatic and terrestrial ecosystems and a comprehensive understanding of lake development and catchment history of the Lake Khamra region.